PENGARUH PRODUK WISATA DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG (Studi pada Pengunjung Objek Wisata Pantai Bondo Jepara) - Ardiyanto, Nidienna Singgih; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2018)
The province of Central Java has a good potential to be developed into tourism areas. One of the tourism object that is developing, namely Bondo Beach in Jepara which has unique tourism potential. But the number of visitors from 2014 to 2016 quite fluctuating, as known in 2014 and 2015 there was an increase in the number of visitors but in 2016 there was a decrease in number of visitors. This study aims to determine the influence of Tourism Products, and Electronic Word of Mouth to Visiting Decision in Bondo Beach Attractions. This type of research is explanatory research. The sample used is 100 respondents. The sampling techniques are accidental and purposive sampling.T he respondent is a Visitor Bondo Beach Attractions who have been visiting the Bondo Beach. The technique analysis are validity and reliability test, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, and test of significance (t-test and F) and SPSS. Based on the results of the analysis is known that the variable Tourism Product contributes influence on Visiting Decision by 36%. Variable Electronic Word of Mouth contributes influence to the Visiting Decision of 45.1%. While simultaneously, The Tourism Product and Electronic Word of Mouth contributes to the influence on Visiting Decision by 53%. This means that the better of Tourism Product and Electronic Word of Mouth the higher the Visiting Decision in Bondo Beach Attractions. Based on that, the researcher suggested that the management of Bondo Beach Objects can pay more attention to the existing tourism products, and improve the toilet feasibility facility, signpost directions so as to facilitate visitors and more active in offering facilities in Bondo Beach information to visitors, so as to increase tourist visit at Bondo Beach.